Beyond church walls : cultivating a culture of care - Rouse, Richard W. (Fortress Press, 2016)
Pastoral care has been traditionally understood as pastoral acts administered to individuals or small groups by an ordained or lay religious practitioner. As congregations in the twenty-first century begin to reclaim the missional nature of church, this view must be broadened to include care and concern for the needs of the larger community. A missional perspective of pastoral care embraces the notion that all of God's people -- not just trained professionals -- are called to partner in the healing and redemption of the world. In Beyond Church Walls, Rick Rouse sets out to articulate precisely what such an approach to pastoral care looks like -- and the substantial impact it can have on congregations and communities. A skilled teacher and pastor with deep experience in real communities, Rouse leads readers through the changing realities of the twenty-first century and to new ways for missional churches to succeed in offering pastoral care for the whole community.